VARIASI ANATOMI DAUN (STOMATA DAN PERTULANGAN DAUN) PADA FAMILI PIPERACEAE DI BANDEALIT TAMAN NASIONAL MERU BETIRI (TNMB) - Sindhy Rohmada Rizgiyya; Sulifah Aprilya Hariani; Pujiastuti Pujiastuti (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
Indonesia is the center of diversity of the Piperaceae family. Piperaceae is often used as traditional medicine, food, ornamental plants, ritual plants and as an economic value for the community. Anatomical utilization of Piperaceae is still not widely done. Therefore, this research is important to find out the members of Piperaceae when viewed from the anatomy of stomata and leaf reinforcement. The purpose of this study was to determine the types of plants of the Piperaceae family found in Bandealit TNMB and to determine variations in stomatal anatomy and leaf reinforcement in the Piperaceae family. The type of research used is descriptive qualitative quantitative research. The results showed that the stomata in the Piperaceae family varied as well as the leaf reinforcement they had. The Piperaceae family found in Bandealit TNMB comes from 2 genera, namely the Piper genus and the Peperomia genus, each of which has varied stomata and leaf reinforcement. Further research needs to be done on stomata and leaf reinforcement in the Piperaceae family.